2000
DOI: 10.1054/bjoc.1999.0989
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in Norwegian testicular cancer patients

Abstract: The intention was to explore the relationship between fertility and testicular cancer, including the possibly treatment-induced changes over time in the post-diagnostic fertility. Data are from the Norwegian Cancer Registry, The Norwegian Population Register and the Population Censuses. By estimating Poisson regression models, birth rates among testicular cancer patients were compared with those of other men who had the same age, parity and duration since previous birth. Poisson regression models were also est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 8 publications
5
43
1
1
Order By: Relevance
“…The total number of children was similar in both groups. This observation completely contradicts the findings of others 34,35 that reported the subfertility of TTPs before, and particularly after the onset of disease. We have no information on family planning and child wish of healthy males and TTPs in this study, however, we may say that the birth rates and fertility indicators in the Hungarian population are much lower than in Nordic countries.…”
Section: Ttps' Offspring Totalcontrasting
confidence: 96%
“…The total number of children was similar in both groups. This observation completely contradicts the findings of others 34,35 that reported the subfertility of TTPs before, and particularly after the onset of disease. We have no information on family planning and child wish of healthy males and TTPs in this study, however, we may say that the birth rates and fertility indicators in the Hungarian population are much lower than in Nordic countries.…”
Section: Ttps' Offspring Totalcontrasting
confidence: 96%
“…Most of this is likely to be a direct effect on germ cell function, but there may also be a contribution from dry ejaculation which was reported as 'quite a bit' or 'very much' in 3% or more patients after chemotherapy compared to surveillance (Figure 1). We do not have direct data comparing fertility rates of our patients with normal controls, but in a study of Norwegian registry data (Fossa and Kravdal, 2000) fertility was approximately 30% lower in testicular cancer patients than the normal population. In line with our findings they reported that lower rates were seen in men who had regional and distant disease (who presumably had more intensive treatment) (fertility rate 0.49 (CI 0.36 -0.64) compared to 1.0 for normal population) rather than patients with local disease (0.85 CI 0.67 -1.06).…”
Section: Discussionmentioning
confidence: 98%
“…The development of testicular cancers is associated with other testicular abnormalities such as testicular maldescent, testicular atrophy and subfertility (United Kingdom Testicular Cancer Study Group, 1994;Moller and Skakkebaek, 1999;Fossa and Kravdal, 2000). Preorchidectomy sperm counts and LH levels are lower and FSH levels higher than age-matched normal controls and patients presenting with lymphoma in a Danish study (Petersen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer has been found to reduce birth rates with an overall effect of about 25 % both in Norway and other countries, probably because of lower fecundity as well as weaker fertility desires (Syse, Kravdal, and Tretli 2007). The strongest effects have been seen for women with gynaecological cancers and men with testicular cancer, though these effects have diminished over time as a result of in vitro fertilization and cryopreservation of semen (Syse, Kravdal, andTretli 2007, Fossa andKravdal 2000). Further, having children increases the partners' benefit from the relationship compared to the alternatives (living alone or with another partner), and many parents may fear that a disruption could harm their child(ren).…”
Section: Fertilitymentioning
confidence: 99%